2006
DOI: 10.1074/jbc.m603627200
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Stress Activates the TAK1-JNK Pathway While Blocking TAK1-mediated NF-κB Activation

Abstract: Osmotic stress activates MAPKs, including JNK and p38, which play important roles in cellular stress responses. Transforming growth factor-␤-activated kinase 1 (TAK1) is a member of the MAPK kinase kinase (MAPKKK) family and can activate JNK and p38. TAK1 can also activate IB kinase (IKK) that leads to degradation of IB and subsequent NF-B activation. We found that TAK1 is essential for osmotic stress-induced activation of JNK but is not an exclusive mediator of p38 activation. Furthermore, we found that altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 38 publications
(48 reference statements)
3
66
0
Order By: Relevance
“…For example, TAO2 can associate with TGF-b activated kinase 1 (TAK1) to inhibit TAK1-mediated activation of NF-kB. 129 TAO2 may regulate TAK1 function through interfering with the interaction between TAK1 and IkappaB kinase. Furthermore, TAO2 does not inhibit the activation of JNK by TAK1, suggesting that TAO2 regulation of TAK1 is important to activate specific intracellular signaling pathways.…”
Section: Other Gcks Relevant To Immune Regulationmentioning
confidence: 99%
“…For example, TAO2 can associate with TGF-b activated kinase 1 (TAK1) to inhibit TAK1-mediated activation of NF-kB. 129 TAO2 may regulate TAK1 function through interfering with the interaction between TAK1 and IkappaB kinase. Furthermore, TAO2 does not inhibit the activation of JNK by TAK1, suggesting that TAO2 regulation of TAK1 is important to activate specific intracellular signaling pathways.…”
Section: Other Gcks Relevant To Immune Regulationmentioning
confidence: 99%
“…TAOk1 interacts with and activates MKK3 leading to activation of p38 (Hutchison et al, 1998). TAOk2 negatively regulates TAK1 activation of the NF B pathway after osmotic stress (Huangfu et al, 2006). TAOk2 associates with MKK3 and MKK6, MAP2Ks upstream of p38 (Chen and Cobb, 2001).…”
Section: Tao Kinase (Taok1 Taok2 Taok3) (Omim#*610266)mentioning
confidence: 99%
“…Human embryonic kidney 293 cells, 293 IL-1RI cells that stably express the IL-1 receptor I [15] were maintained as described previously [14]. Mouse keratinocytes were described previously [16].…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…We have previously shown that the TAO2 kinase can interfere with the interaction of TAK1 and IKK, resulting in the inhibition of the NF-jB pathway. However, knockdown of TAO2 was observed to have only a partial effect on relieving inhibition of NF-jB [14]. This suggests that NF-jB activation is blocked by additional mechanisms that function under conditions of osmotic stress.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation